Leading IT projects : the IT manager's guide - Keyes, Jessica, 1950- (Auerbach ; Taylor & Francis [distributor], 2008)
Senior level IT managers are often responsible for a wide variety of development projects. This book presents a complete tutorial on project management along with information on project manager skill sets.